Rancang Bangun Sistem Pakar untuk Deteksi Dini Katarak Menggunakan Algoritma C4.5 - Ivana Herliana W. Jayawardanu; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
In 2010, 51% of 39 million blindness are caused by cataract. In 2013, there are 1.8% of 1.027.763 Indonesian people who suffered from cataract. Half of them are not treated yet due to their ignorance on the cataract disease. Therefore, in this research, we tried to build a system that can detect early cataract disease as the ophthalmologist would do. The system will use C4.5 algorithm that receives 150 training data set as an input, resulting in a set of rules which can be used as decision factors. To test the system, k-fold cross validation technique is been used with k equals to 10. From the analysis result, the accuracy of the system is 93.2% to detect cataract disease and 80.5% to detect the type of cataract disease one might suffered. Index terms-C4.5 algorithm, cataract, k-fold cross validation, machine learning